TRAINING FOR SKILL ACQUISITION: AN ANTIDOTE FOR EFFECTIVE POVERTY REDUCTION IN NIGERIA - Maigida, J. F.; Raymond, E. (Sokoto Educational Review, 2014)
Poverty is a major focus of concern and an active area of research and policy debate. It is a central problem in development studies because it has been discovered to be rampant in developing countries including Nigeria. The incidence of poverty has been on the increase. Present concern for poverty and poverty reduction worldwide has resulted in both international and domestic initiatives to reduce the miseries of the poor. This paper focuses on the need for training in skill acquisition to all those who need and can use skills as a means for tackling the problem of unemployment and underemployment thereby reducing the incidence of poverty and unemployment in Nigeria.